Between consultation and control: how incubators perform a governance function for entrepreneurial firms. Issue 9 (14th February 2023) - Flanschger, Andreas; Heinzelmann, Rafael; Messner, Martin
Abstract : Purpose: This paper examines the governance function that incubators perform for entrepreneurial firms. The authors demonstrate that this governance function has both a consultative and a control dimension and illustrate how these are enacted in the interactions between incubators and entrepreneurs. The authors also show how these interactions come into being and how entrepreneurs assess the value of the governance role played by incubators. Design/methodology/approach: The paper is based on a cross-sectional interview study with entrepreneurs of 21 start-ups that were hosted by three different incubators. The start-ups are all early-stage technology firms. The analysis in the paper follows an inductive approach. Findings: The authors find that the governance role of incubators is about both consultation and control. Consultative forms of governance include providing input and advice as well as questioning ideas and assumptions. Controlling forms of governance comprise setting targets and tracking progress as well as enforcing structures and documentation. The authors furthermore show that governance episodes are triggered either by the entrepreneurs themselves or by the incubator. In the former case, such episodes are mainly about consultation, while in the latter one, they often have a pronounced control element, which materializes particularly through regularly enforced meetings. Most entrepreneurs seem to appreciate this control element, acknowledging that, in its absence, they would lack the self-discipline of doing some things that need to be done. Research limitations/implications: This study's findings extend prior research on inter-organizational relationships and the types of governance mechanisms observed therein. The authors show that a strict separation between actors who offer consultation and those who exercise control is too simplistic. Incubators influence entrepreneurial firms both through consultative and controlling forms of governance. In terms of limitations, this study's analysis focuses on the perspectives of entrepreneurs, and the authors did not include the perspectives of incubators nor did the authors directly observe meetings between these two parties. Practical implications: This paper provides examples for how entrepreneurial firms can benefit from being part of an incubator. Originality/value: This study contributes to the discussion of the governance of inter-organizational relationships by focusing on incubators. In so doing, the authors also complement extant literature on management control in entrepreneurial settings by showing how the incubator fulfills a control function for entrepreneurs before these implement control mechanisms themselves.